Role of adenosine on the resistance to temozolomide anti-tumor agent in glioblastoma - Nogueira, Vanda Cristina Simões (2020)
Glioblastoma is a primary brain tumor of glial cells with a high incidence in adults and is one of the most abundant brain cancer pathologies. This type of tumor is associated with high genomic instability caused by global hypomethylation of the DNA, that induces activation of oncogenes, loss of imprinting and increased genomic instability. Adenosine is a purine nucleoside important to neuroprotection, neuromodulation, synaptic plasticity and immunomodulation. In hypoxic and stress regions in the brain tumors, commonly found in glioblastoma, factors induced by hypoxia (HIF) are activated. These factors modulate the expression of different proteins, particularly the CD39 and CD73. These enzymes are involved in the metabolism of adenosine, increasing the formation of this nucleoside extracellularly. Increased extracellular levels of adenosine lead to increased adenosine uptake into the cell by nucleoside transporters, producing accumulation of intracellular adenosine. Increased intracellular levels of adenosine or homocysteine lead to an increase of Sadenosylhomocysteine (SAH) levels and a decrease of the S-adenosylmethionine (SAM)/SAH ratio, since the reaction of adenosine with homocysteine to give SAH, catalyzed by SAH hydrolase, is near equilibrium. SAH is a competitive inhibitor of SAMdependent methyltransferases, its accumulation causing global hypomethylation of DNA. The O-6-methylguanine-DNA methyltransferase (MGMT) is a DNA repair protein whose function is to remove methyl groups from the guanines in DNA. Although, very different mutations can cause the lack of MGMT expression, the hypermethylation of MGMT gene promoter is the main responsible for this. Early mutations in glioblastoma frequently lead to hypermethylation in the MGMT gene promoter, which causes gene silencing and lack of expression of the MGMT DNA repairing protein. It is known that the expression of this tumor suppressor protein is responsible for the lack of glioblastoma’s sensitivity to available first-line treatment, the alkylating drug Temozolomide (TMZ). TMZ is an alkylating agent used in glioblastomas treatment, usually combined with radiotherapy. However, the success of this agent is very low, above 20 % response rat, and the prognosis of the glioblastoma patients around one year. The TMZ effect is influenced by several factors inside the cell, like DNA mismatch repair system, MGMT expression, and base excision repair system. The expected final effect of TMZ is the apoptosis of the glioblastoma cells. Another important effect is the acquired resistance which happens after the first treatment with TMZ in many patients. In vitro, different mechanisms became active after a first TMZ treatment, like an increase of MGMT expression and mutations in the DNA mismatch repair system proteins. The aim of this study is to understand if there is a relationship between the increased intracellular adenosine, associated with global hypomethylation of DNA, and the chemotherapeutic resistance to TMZ caused by an increased in MGMT expression and activity. Three glioblastoma cell lines, U87, U373, and SNB19 were used. Intracellular adenosine levels were increased by incubating cells for 72h with ABT 702 dihydrochloride (ABT, 15µM), an adenosine kinase inhibitor. TMZ (100 and 500 µM) was added for the last 1, 2, 3, 24 and 48 hours of incubation. MGMT expression and localization were visualized by immunocytochemistry and western blot, respectively. Cell viability/proliferation was assessed by CCK8 assay. The results by western blot analysis showed that increased levels of adenosine do not affect MGMT expression. A decrease in cell viability/proliferation was observed after treatment with ABT in U373 cell line. After immunocytochemistry against active caspase 3, a marker of cell apoptosis, it was possible to see that the decrease of cells number produced by ABT is due to a decrease in cell proliferation and not cell apoptosis. TMZ (500 µM) was able to decrease the cell viability/proliferation in SNB19 and U373 cell lines. We prove by immunocytochemistry that this effect involves cell death mechanisms mediated by caspase 3 activation, like apoptosis. The combined treatment with TMZ plus an inhibitor of MGMT, we visualized a more accentuated effect on cell survival, but the relative effect of TMZ was not affected because the inhibitor causes its own cytotoxicity. Increasing levels of adenosine with ABT did not modified the TMZ effect on cell survival in U373 cell line, but in SNB19 cell lines seems to be a recovery of cell survival after combined treatment with ABT and TMZ.